Contextualized Islamic Family Law in Practice: Divorce and Child Custody Disputes in Cikarang, Indonesia - Siti Ropiah; Syafi'i Syafi'i (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2026)
The practice of Islamic family law in Indonesia is shaped not only by formal legal norms but also by social, economic, and cultural realities. This interaction is particularly salient in Cikarang, Bekasi, where divorce and child custody disputes reveal how legal norms are interpreted, adapted, and negotiated in real contexts. This study explores how Islamic family law is applied in a contextualized manner in the resolution of divorce and child custody disputes in Cikarang, with special focus on the role of religious courts in integrating legal norms with local socio-cultural conditions. Using a qualitative case study design, data were gathered through in-depth interviews with religious court judges, legal practitioners, and litigants, alongside analysis of court decisions and relevant legal documents. Thematic analysis was used to uncover recurring patterns and interpretive logics in judicial practice. The findings indicate that although religious courts provide an institutional structure for handling family disputes, judicial decisions are significantly shaped by socio-economic conditions, cultural expectations, and extended family involvement. Mediation emerged as the dominant mechanism for divorce resolution, reflecting both normative values (sulh, maslahah) and pragmatic considerations. Child custody outcomes varied according to welfare considerations, economic capacity, and child preferences rather than rigid textual interpretations. This study contributes to the socio-legal and Islamic law scholarship by demonstrating that Islamic family law operates as a living legal system shaped by social realities, not merely as formal doctrinal norms. It expands theoretical understanding of how law is negotiated in practice within plural legal environments and highlights the flexibility and contextual adaptability of Islamic legal interpretation. The study also offers empirical evidence that informs debates on legal pluralism and judicial discretion in Muslim-majority contexts. The findings underscore the need for strengthening public legal literacy, enhancing mediation and judicial training, and fostering institutional collaboration to improve access to justice. Practical emphasis on child welfare and humanistic legal approaches can further ensure substantive justice for families.